The Impact of Long COVID on Language Proficiency Across Different School Levels in Hong Kong - Xu, Shebe S. (Archīum Ateneo, 2025)
Long COVID, where symptoms persist after recovering from COVID-19, can affect cognitive functions like language. However, little is known about its impact on children’s language skills, especially across different school levels. This study investigated the impact of long COVID on language proficiency among 1244 children (Asian; 53.5% boys) from kindergartens (N = 408, Mage = 4.42 ± 1.26 years), primary schools (N = 547, Mage = 9.69 ± 1.96 years), and secondary schools (N = 289, Mage = 14.97 ± 1.85 years) in Hong Kong. Language proficiency was assessed using the Language Experience and Proficiency Questionnaire (LEAP-Q), which measured speaking, listening, reading, and writing in both Chinese and English. Participants were categorized into three groups: long COVID, recovered from COVID-19, and no history of COVID-19. One-way and two-way ANOVAs were used to analyze the differences in language proficiency across these groups and school levels. Children with long COVID symptoms exhibited significantly lower overall language proficiency, particularly in speaking and listening, compared to those in the recovered and no-COVID groups. The effect was more pronounced among primary and secondary students, with secondary school students showing the most substantial deficits. No significant differences were found between the recovered and no-COVID groups. The results suggest that long COVID might have detrimental effects on children’s linguistic proficiency. The language development of older students who suffered from long COVID could benefit from receiving targeted educational and therapeutic interventions.